Understanding Change
XIV, 314 p.
Keywords: What can economics, the natural and the social sciences learn from each other in better understanding complex forms of change? How far can models, methodologies or metaphors that have been used successfully in one disciplinary field be 'exported' and meaningfully applied to other fields? Distinguished researchers from across the globe assess, in a rare example of successful cross-disciplinary engagement, the explanatory power of chaos theory, new evolutionary theory, path dependency, neo-institutional economics, multiple modernities and historical institutionalism. The book provides an exciting panorama of state of the art thinking and new avenues to combining the power of various traditions of thought.